ASSESSMENT OF THE STRUTURE OF FOREST IN BURITICUPU URBAN HOMEGARDENS, ON THE AMAZON REGION OF MARANHÃO, NORTHEASTERN BRAZIL - Cordeiro, Rogério Soares; Souza, Fabiane Barreto; Santos, Francisco Maciel Barbosa; Cajaiba, Reinaldo Lucas (Revista da Sociedade Brasileira de Arborização Urbana, 2024)
Homegardens play a vital role in urban ecosystems, impacting climate regulation, soil conservation, and biodiversity. Investigating these microecosystems is crucial for better understanding their role in biodiversity conservation. This study assessed the diversity and structure of urban homegardens in Buriticupu, a city in the Amazon biome, Maranhão, Brazil. Information on tree species in the homegardens, including taxonomy (richness, abundance, diversity, and equitability), ecological aspects (use and origin), and structural characteristics (size and crown area), was collected. The sampling of 51 homegardens yielded 476 trees from 26 botanical families and 62 species. Cocos nucifera, Mangifera indica, and Carica papaya were the most common species. Edible species predominated, and exotic species represented 63.07% of the recorded species. Homegarden size was positively correlated with species richness, diversity, and abundance. The variations in composition and species richness between the homegardens are likely linked to terrain size and property owner planting preferences. Urban homegardens in Buriticupu, particularly native species used for food, were found to contribute significantly to tree biodiversity conservation. However, the prevalence of exotic species raises concerns about their potential impacts on natural Brazilian ecosystems. These findings emphasize the importance of managing urban homegardens to balance biodiversity conservation and exotic species introduction.